REPRESENTASI HUMOR SARKASME PADA VIDEO YOUTUBE UNCLE ROGER - Fella Rahmah Putri; Ida Ri'aeni; Ririn Risnawati (JIKE: Jurnal Ilmu Komunikasi Efek, 2022)
A comedian has a function to entertain the audience. He displays interesting content and can lead the audience to laugh. Humor put forward by comedians consists of aspects of verbal actions carried out by speakers which we usually call aspects of the mouth and nonverbal aspects, namely with other body movements which are stimulating, cognitive and intellectual activities as assessment and evaluation as well as those that are visible from smiles and laughter. . It is interesting to study with semiotic method. Semiotics is the science or method of analysis to study signs. Semiotics has various types, one of which is Social Semiotics. This research is about sarcasm humor in Uncle Roger's Youtube video content entitled "Uncle Roger is Sick of Nasi Goreng Eggs (BBC Food). Researchers analyzed the video by connecting representation theory and MAK Halliday's social semiotic theory who saw that the text contains three important components, namely: Discourse, Discourse Tenor and Discourse Mode Based on the analysis of social semiotics, the results of the research are: (1) There are 14 Discourse Fields discussed by Uncle Roger in the video entitled "Uncle Roger is sick with Egg Fried Rice (BBC Food)"; (2) People involved in the discourse in the Youtube video is chef Hersha Patel who is under the auspices of the BBC Food portal and involves Asian culture in cooking egg fried rice compared to white or western culture (3) The discourse in this video uses a sarcasm style. used, is a discourse that contains sarcasm or full of innuendo and ridicule directly or indirectly . Uncle Roger is also a hyperbole, figure of speech, and personification. Keywords: social semiotics, sarcasm humor, youtube videos.